The Influence of Insulin, ß-Estradiol, Dexamethasone and Thyroid Hormone on the Secretion of Coagulant and Anticoagulant Proteins by HepG2 Cells - Niessen, René W L M; Pfaffendorf, Birgit A; Sturk, Augueste; Lamping, Roy J; Schaap, Marianne C L; Hack, C Erik; Peters, Marjolein (Thrombosis and Haemostasis, 1995)
As a basis for regulatory studies on the influence of hormones on (anti)coagulant protein production by hepatocytes, we examined the amounts of the plasma proteins antithrombin III (AT III), protein C, protein S, factor II, factor X, fibrinogen, and prealbumin produced by the hepatoma cell line HepG2, into the culture medium, in the absence and presence of insulin, β-estradiol, dexamethasone and thyroid hormone. Without hormones these cells produced large amounts of fibrinogen (2,452 ± 501 ng/mg cell protein), AT III (447 ± 16 ng/mg cell protein) and factor II (464 ± 31 ng/mg cell protein) and only small amounts of protein C (50 ± 7 ng/mg cell protein) and factor X (55 ± 5 ng/mg cell protein). Thyroid hormone had a slight but significant effect on the enrichment in the culture medium of the anticoagulant protein AT III (1.34-fold) but not on protein C (0.96-fold) and protein S (0.91-fold). This hormone also significantly increased the amounts of the coagulant proteins factor II (1.28-fold), factor X (1.45-fold) and fibrinogen (2.17-fold). Insulin had an overall stimulating effect on the amounts of all the proteins that were investigated. Neither dexamethasone nor ß-estradiol administration did substantially change the amounts of these proteins.We conclude that the HepG2 cell is a useful tool to study the hormonal regulation of the production of (anti)coagulant proteins. We studied the overall process of protein production, i.e., the amounts of proteins produced into the culture medium. Detailed studies have to be performed to establish the specific hormonal effects on the underlying processes, e.g., transcription, translation, cellular processing and transport, and secretion.